Cytotoxic Activity Of Non Polar Fraction From Annona Muricata L. Leaves On Hela And Raji Cell Line - Anif Nur Artanti; Okid Parama Astirin; Adi Prayitno (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2016)
The main focus of the research is cancer by a viral infection such as nasopharinx and cervical cancer that have high incidence in Indonesia. Cervical cancer is due to the viral infection known as the Human Papilloma Virus (HPV) and nasopharing cancer is a cancer that is caused by EBV infection (Eppstein Barr virus). The main priority of nasopharinx  and servix cancer treatment is the use of chemotherapeutic agents, but it might also lead to diverse side-effects. The focus of this study was to develop the potency of non polar fraction from Annona muricata L. leaves by observing the cytotoxic effect on Hela and Raji cancer cell line.